2021
DOI: 10.1038/s41467-021-26303-x
|View full text |Cite
|
Sign up to set email alerts
|

A C. elegans model of C9orf72-associated ALS/FTD uncovers a conserved role for eIF2D in RAN translation

Abstract: A hexanucleotide repeat expansion GGGGCC in the non-coding region of C9orf72 is the most common cause of inherited amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Toxic dipeptide repeats (DPRs) are synthesized from GGGGCC via repeat-associated non-AUG (RAN) translation. Here, we develop C. elegans models that express, either ubiquitously or exclusively in neurons, 75 GGGGCC repeats flanked by intronic C9orf72 sequence. The worms generate DPRs (poly-glycine-alanine [poly-GA], poly-glycine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Furthermore, these results support a novel model of pathogenicity in human diseases, where repeat expansions located in ill-defined upstream ORFs can be decoded into novel and toxic proteins through translation initiation at nearcognate start codons. Interestingly, a similar mechanism was recently identified in amyotrophic lateral sclerosis and frontotemporal dementia, where an expansion of G4C2 repeats located in the first intron of the C9ORF72 gene is translated into a polyglycine-alanine dipeptide repeat (polyGA DPR) protein through translation initiation at a CUG near-cognate start codon located 24 nucleotides upstream of the repeats (Green et al, 2017;Tabet et al, 2018;Sonobe et al, 2018;Almeida et al, 2019;Boivin et al, 2020;Sonobe et al, 2021;Figure 3). It remains to determine whether these examples of translation initiation at near-cognate start codons are two isolated cases or reflect a more global mechanism of disease.…”
Section: Fragile X-associated Tremor/ Ataxia Syndromementioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, these results support a novel model of pathogenicity in human diseases, where repeat expansions located in ill-defined upstream ORFs can be decoded into novel and toxic proteins through translation initiation at nearcognate start codons. Interestingly, a similar mechanism was recently identified in amyotrophic lateral sclerosis and frontotemporal dementia, where an expansion of G4C2 repeats located in the first intron of the C9ORF72 gene is translated into a polyglycine-alanine dipeptide repeat (polyGA DPR) protein through translation initiation at a CUG near-cognate start codon located 24 nucleotides upstream of the repeats (Green et al, 2017;Tabet et al, 2018;Sonobe et al, 2018;Almeida et al, 2019;Boivin et al, 2020;Sonobe et al, 2021;Figure 3). It remains to determine whether these examples of translation initiation at near-cognate start codons are two isolated cases or reflect a more global mechanism of disease.…”
Section: Fragile X-associated Tremor/ Ataxia Syndromementioning
confidence: 62%
“…Similarly, G4C2 and G3C2T repeat expansions are translated into toxic poly(glycine-alanine)- and poly(glycine-proline)-containing proteins in ALS/FTD and SCA36, despite these repeats being localized in the first intron of the C9ORF72 and NOP56 genes, respectively. These intronic regions are unspliced in patients and, alike in FXTAS and NIID, repeat expansions are translated through initiation at canonical AUG, or near-cognate, start codons located upstream of the repeats ( Green et al, 2017 ; Tabet et al, 2018 ; Sonobe et al, 2018 ; Almeida et al, 2019 ; Boivin et al, 2020 ; McEachin et al, 2020 ; Sonobe et al, 2021 ; Figure 3 ). These results are reminiscent of pioneering studies showing that CAG expanded repeats located within the ATXN8 and JPH3AS RNAs, which were initially considered as long non-coding RNAs but were later on found to be carrying small ORFs, are translated through canonical ATG-initiated translation into toxic polyglutamine proteins in SCA8 and HDL2 ( Moseley et al, 2006 ; Wilburn et al, 2011 ; Figure 3 ).…”
Section: Oculopharyngodistal Myopathy With Leukoencephalopathy: the M...mentioning
confidence: 99%
“…Insights describing the involvement of RAN translation products in the pathogenesis of particular REDs are beyond the scope of this review and were presented elsewhere (Banez-Coronel & Ranum, 2019). It is worth noting that so far deleterious properties of RAN peptides were mostly observed in experiments based on artificial cellular or animal models (e.g., Sellier et al, 2017;Sonobe et al, 2021;Todd et al, 2013). Indeed, RAN proteins were identified in several patient's samples (Ash et al, 2013;Bañez-Coronel et al, 2015;Mori, Weng, Arzberger, May, Rentzsch, Van Broeckhoven, et al, ;Sellier et al, 2017;Todd et al, 2013;Zu et al, 2013Zu et al, , 2017, however, our knowledge about toxicity of those endogenously expressed peptides is limited (Freibaum & Taylor, 2017).…”
Section: Ran Translationmentioning
confidence: 99%
“…In addition, it was shown that overexpression of Drosophila 5MP homolog in FXTAS flies reduced RAN peptides-mediated toxicity (Singh et al, 2021). Recently, Sonobe et al (2021) developed a new C. elegans model of C9-ALS/FTD. The study showed that loss-of-function mutations of eIF2D lead to reduced production of polyGA (and to lesser extent polyGP), positively affecting locomotor function, and lifespan of transgenic worms (Sonobe et al, 2021).…”
Section: Ran Translationmentioning
confidence: 99%
See 1 more Smart Citation